Impact of heat-inactivated Lactobacillus casei and Lactobacillus paracasei strains on cytokine responses in whole blood cell cultures of children with atopic dermatitis - Cukrowska, B; Rosiak, I; Klewicka, E; Motyl, I; Schwarzer, M; Libudzisz, Z; Kozakova, H (Folia microbiologica, 2010)
Heat-inactivated Lactobacillus casei LOCK 0900, L. casei LOCK 0908 and Lactobacillus paracasei LOCK 0919 strains, applied to blood cell cultures obtained from children with atopic dermatitis induced production of anti-allergic T(H)1 cytokines (interleukin-12, interleukin-18, interferon-gamma, tumor necrosis factor-alpha) and regulatory transforming growth factor-beta(1)), but did not stimulate pro-allergic interleukin-5. The lactobacilli-mixture remarkably enhanced the T(H)1 response compared to single strains. This synergistic effect was not observed for transforming growth factor-beta(1). In contrast, the amount of interleukin-10 was found to be considerably lower when cells were stimulated with lactobacilli-mixture compared to single strains. The mixture of Lactobacillus strains represents a probiotic bacterial preparation modulating in vitro cytokine profile of allergic children towards anti-allergic T(H)1 response.
Keywords: kojenec; Infant; Lactobacillus; cytokiny; Probiotics; Immunologic Factors; atopická dermatitida; kultivované buňky; Cells, Cultured; Cytokines; Leukocytes, Mononuclear; imunologické faktory; lidé; Dermatitis, Atopic; Humans; leukocyty mononukleární; probiotika